PENGARUH MODEL PROJECT BASED LEARNING TERHADAP KETERAMPILAN PROSES SAINS PADA PEMBELAJARAN IPA MATERI SISTEM PEREDARAN DARAH MANUSIA DI KELAS V SD GMIT MANUMUTI - Markus Sampe; Paulina Riwu Ga; Harlyanti Benu (Universitas Nusa Cendana, 2022)
This study discusses the effect of the Project Based Learning model on science process skills. The background of this research study is the low science process skills of students in science learning and learning that still uses conventional models. The purpose of this research is to examine the effect of the Project Based Learning learning model on science process skills. The type of research used is quantitative. The research method uses the One Group Pretest Posttest Design with the Pre-Experimental research design. The instruments used were observation sheets, student worksheets, and science process skills questionnaire sheets which were used as pre-test and post-test. The sampling technique in this study is by taking simple random sampling, the sample used is 1 class, namely VA. The research was conducted at SD GMIT Manumuti, Kupang Regency. Based on the research, it was found that from all indicators of students' science process skills, the results of calculating the independent t-test hypothesis using SPSS 22 obtained the results seen from Sig. (2-tailed) < α 0.05, namely 0.00, this shows that H0 is rejected and H1 is accepted. This means that the Project Based Learning (PjBL) learning model has a significant influence on science process skills.